Natural history of intraductal papillary mucinous neoplasm and non‐neoplastic cyst: long‐term imaging follow‐up study. (19th June 2017) - Hisada, Yuya; Nagata, Naoyoshi; Imbe, Koh; Takasaki, Yusuke; Sekine, Katsunori; Tajima, Tsuyoshi; Yanase, Mikio; Fujimoto, Kazuma; Akiyama, Junichi; Uemura, Naomi
Abstract: Background: To identify differences in incidence and mortality of pancreatic cancer (PC) between intraductal papillary mucinous neoplasm (IPMN) and non‐neoplastic cyst. Methods: Patients with pancreatic cyst ( n = 526; 263 with IPMN and 263 with non‐neoplastic cyst matched for age, sex, and diagnosis year) were periodically followed‐up with imaging. Hazard ratio (HR), standardized incidence ratio (SIR), and standardized mortality ratio (SMR) for PC and PC‐related mortality were estimated. Results: During a mean follow‐up of 57.5 months with 3, 376 computed tomography scans and 1, 079 magnetic resonance imaging scans, 5‐year cumulative PC incidence was 4.0% for IPMN and 0% for non‐neoplastic cyst, respectively (HR 5.2; P = 0.031). During a mean follow‐up of 73.1 months, 5‐year cumulative PC‐related mortality was 2.6% for IPMN and 0% for non‐neoplastic cyst, respectively (HR 4.5; P = 0.05). Compared with the general population in Japan, patients with IPMN, but not those with non‐neoplastic cyst, had significantly increased risks of PC incidence (SIR 22.03) and related mortality (SMR 15.9). Conclusions: During long‐term imaging follow‐up, patients with IPMN developed PC over time, whereas none of the patients with non‐neoplastic cyst developed it within 5 years. Compared with the general population, patients with IPMN, but not those with non‐neoplastic cyst, were at risk of PC and related mortality. Highlight: In this long‐term imaging follow‐up study, Hisada and colleagues demonstrated that patients with intraductal papillary mucinous neoplasm (IPMN) had significantly higher incidence of pancreatic cancer and related death than patients with non‐neoplastic cyst. Compared with the general population, patients with IPMN, but not those with non‐neoplastic cyst, were at increased risk.